AN ASSESSMENT OF THE ADHERENCE TO GUIDELINES FOR THE MANAGEMENT OF ASTHMA EXACERBATIONS IN SELECTED PRIMARY HEALTHCARE FACILITIES IN THE WESTERN CAPE - Nikodem, Cheryl (Journal of Community and Health Sciences, 2020)
Introduction: Asthma is described as a chronic inflammatory disorder of the airways. Recurrent episodes of "acuteattacks" or exacerbation may occur in susceptible individuals. The onset of these episodes maybe associated with external stimuli such as cold or pollen. Asthma could be a controllable disorder and most people with asthma should be able to lead a normal, productive life if their asthma is managed effectively. A review of literature recommend that adherence to uniform guidelines on asthma management can reduce the frequency of acute attacks. Guidelines for the management of asthma have been implemented in health care facilities in the Western Cape for more than a decade. Objective: The objective of this study was to investigate the extent to which doctors adhere to the prescribed asthma guidelines. Method: Record review. Participants: Forty records were reviewed. Setting: The study was conducted at four Primary Health Care (PHC) centres in the Western Cape. Intervention: A review of patient records was done to examine adherence to the implementation of the recommended guidelines. Results: The results are in line with the literature which shows that adherence to the asthma guidelines is sub optimal. Conclusion: It is recommended that authorities should regularly follow health care facilities to evaluate to what extend guidelines are adhered to and ongoing training should be given to make health workers aware of these guidelines.